Features and rhizosphere colonization strategies of Lactobacillus plantarum 0308 in soil-tomato systems - Zhang, Xiancui; Liao, Haoran; Cai, Tong; Cai, Peiwen; Wu, Xiangyu; Wang, Zhe; Ma, Haoyu; Qiu, Guoqiang; Zhao, Mingxing; Lu, Xingmeng; Wang, Xianting; Wu, Choufei (Frontiers in Microbiology, 2025)
IntroductionThe lactic acid bacteria (LAB) has shown great potential as a sustainable solution to support agriculture through its plant-growth-promoting and biocontrol activities. However, their efficacy as bioinoculants is limited by unpredictable colonization in natural conditions.MethodsThe bacterial strain LP0308, identified as Lactobacillus plantarum (LP0308) based on 16S rRNA sequence analysis, was obtained from rhizosphere soil. The features and colonization strategies of LP0308 were characterized through genome sequencing, tomato seed germination assays, pot experiments, and measurements of soil physicochemical properties and enzyme activities.ResultsLP0308 was introduced into the soil of tomato, and it could stably persist and proliferate for a long-term (0–20 days), as confirmed by colony-forming unit (CFU), quantitative real-time PCR (RT-qPCR), and fluorescence in situ hybridization (FISH) analyses. Further characterization revealed that LP0308 altered the microbial composition of the rhizosphere soil and significantly increased the abundance of Bacillus and potentially pathogenic microorganism. Further analyses revealed that LP0308 altered the rhizosphere soil microbial community, significantly increasing the abundance of Bacillus spp. while decreasing the potential pathogenic microorganisms, such as Ralstonia solanacearum and Fusarium oxysporum. In addition, the successful colonization of LP0308 led to drastically increased expression of encoding biofilm (vpsI1, vpsI2, vpsC, and vpsI3), immune modulation (pbpG, kdtB, and wbpL), and antimicrobial activity gene (farB). L. plantarum strain LP0308 was confirmed as a possible plant growth-promoting rhizobacteria (PGPR), which significantly promoted bud length, plant height, primary root length, root fresh weight, and whole-seedling fresh weight. Additionally, application of LP0308 markedly improved soil nutrient availability and stimulated key enzymatic activities.DiscussionTogether, our findings suggest the LP0308 as a potential target for developing more effective bioinoculants for sustainable agriculture.